2017
DOI: 10.1136/bmjpo-2017-000008
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for quality improvement programme to reduce central line-associated bloodstream infections in NICU of low and middle income country

Abstract: IntroductionCentral line-associated bloodstream infections (CLABSI) are the most important cause of morbidity and mortality in critically ill patients. Evidence-based interventions when used in form of a bundle have proven to decrease CLABSI. Our unit has a high CLABSI rate (9/1000 central line days). Therefore, we intend to introduce evidence-based CLABSI prevention package in our practice to improve CLABSI rates in our NICU within limited resources.Methods and analysisThe study will be conducted using preana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…During implementation of the preventive measures, limitations of human resources affect also the compliance with the prevention guidelines, as shown by a study in Jordan where the nurse to patient ratio of 1:1 was the only predictor of higher compliance with the guidelines (Aloush and Alsaraieh, 2018). Effective strategies may be used to overcome this challenge during interventions, including assigning a nurse as a unit-based quality nurse (Thom et al, 2014), or assembly of an intervention team of physician, infection control nurse, and ICU nurse to assess and follow up CLABSI cases (Hussain et al, 2017).…”
Section: Limited-resource Settingsmentioning
confidence: 99%
“…During implementation of the preventive measures, limitations of human resources affect also the compliance with the prevention guidelines, as shown by a study in Jordan where the nurse to patient ratio of 1:1 was the only predictor of higher compliance with the guidelines (Aloush and Alsaraieh, 2018). Effective strategies may be used to overcome this challenge during interventions, including assigning a nurse as a unit-based quality nurse (Thom et al, 2014), or assembly of an intervention team of physician, infection control nurse, and ICU nurse to assess and follow up CLABSI cases (Hussain et al, 2017).…”
Section: Limited-resource Settingsmentioning
confidence: 99%
“…A previous study has demonstrated the role of using “Bundles” for controlling CLABSI [ 18 ]. In one study, the zero-sepsis rate for 1000 days was achieved and was attributed to adopting the “Bundle care approach.” [ 21 ] In another study by Asad Latif et al., the combined use of exclusive maternal milk and adopting Bundle care approach led to reduction in various morbidities including reduced rate of culture-positive sepsis in VLBW babies [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The infection cannot be related to any other infection the patient might have and must not have been present or incubating when the patient was admitted to the facility. CLABSI rate is the total number of CLABSI divided by the total number of device days 1000 11 12…”
Section: Methodsmentioning
confidence: 99%